Caregiver's Country of Birth Is a Significant Determinant of Accurate Perception of Preschool-Age Children's Weight. (April 2016) - Natale, Ruby; Uhlhorn, Susan B.; Lopez-Mitnik, Gabriela; Camejo, Stephanie; Englebert, Nicole; Delamater, Alan M.; Messiah, Sarah E.
Background . One in four preschool-age children in the United States are currently overweight or obese. Previous studies have shown that caregivers of this age group often have difficulty accurately recognizing their child's weight status. The purpose of this study was to examine factors associated with accurate/inaccurate perception of child body mass index (BMI) among a multicultural sample of caregivers who were predominantly low-income and foreign-born. Methods . A total of 980 caregivers (72% Hispanic, 71% born outside of the United States) of preschool-age children ( N = 1, 105) were asked if their child was normal weight, overweight, or obese. Answers were compared to actual child BMI percentile category via chi-square analysis. Logistic regression analysis was performed to assess predictors of accurate perception of child BMI percentile category. Results . More than one third of preschoolers were either overweight (18.4%) or obese (16.5%). The majority (92%) of caregivers of an overweight/obese child inaccurately perceived that their child was in a normal BMI category. Overall, foreign-born caregivers were significantly less likely to accurately perceive their child's BMI percentile category versus U.S.-born caregivers (odds ratio [OR] = 0.65, 95% confidence interval [CI] = 0.48-0.88). Specifically, those born in South America (OR = 0.59, 95% CI = 0.36-0.98), Central America/Mexico (OR = 0.59, 95% CI = 0.41-0.85), and Caribbean Hispanic nations (OR = 0.54, 95% CI = 0.35-0.83) were significantly less likely to accurately perceive their child's BMI category versus U.S.-born caregivers. Conclusions . The results of this study suggest that foreign-born caregivers of U.S. preschool-age overweight/obese children in particular do not accurately perceive their child's BMI status. Health care professionals serving foreign-born caregivers may consider additional culturally appropriate healthy weight counseling for these families.